The deficient regulation of judicial inspection in the Peruvian Code of Civil Procedure: Gaps and reform proposals - Muriche Astorayme, Cesar (2025)
This research article focuses on the legal and normative analysis of judicial inspections in Peru, critically examining their current regulation. The study identifies and discusses the shortcomings and gaps in the legal provisions of the Peruvian Code of Civil Procedure and proposes solutions for future legislation. Structural problems are critically analyzed, particularly the lack of clear normative limits regarding dignity and bodily privacy, the absence of a specific procedure for judicial inspections in collegiate courts, the lack of provisions for the use of new technologies, such as drones, and the inspection of electronic documents. The methodology employs comparative law as a tool to support the need for legislative reform.